Insights into the Peculiarities of Verbal Lexical Semantic Groups in Related Languages: On the Material of Polish and Belarusian Defence Verbs - Litvinovich, Anzhalika H. (Slavia Orientalis, 2025)
The aim of the study is to identify the features of the implementation of denotative and causative semantics within one lexical-semantic group (LSG) of verbs in related languages. The analysis of the LSG of defence in Polish and Belarusian showed that the same area of semantics has different configurations of the expression plan. Defence verbs, in addition to the denotative meaning, contain a causative component in their semantic structure. Defence verbs do not have regular formal means of expressing causative semantics. These verbs do not demonstrate a direct correlation between the denotative and causative components. Polish and Belarusian causative verbs expand the list of causation types. Principles of causation coding, common for both languages, are influenced by national peculiarities of reflecting reality.